Electromagnetic Characteristic Analysis of Circuit Breaker Actuator Using Bond Graph Method. Issue 6 (3rd April 2017) - Tseng, Kuo-Hsiung; Chou, Chih-Ju; Liu, To-Cheng; Wu, Chun-Da; Chiu, Juei-Long; Cheng, Pei-Yu
Abstract: This study analyzed the characteristics of the electromagnetic actuator in a circuit breaker according to the bond graph method. Such analysis is particularly useful in describing the dynamic hybrid systems of electromagnetic actuators, including the electrical, magnetic, and mechanical fields. The bond graph method provided a way to design and revise a model by observing its energy transference and physical structure. The bond graph method could be converted into a Simulink model in order to compare the measured data with the simulation results. Based on the combined features of hybrid systems from the bond graph method, a magnetic time constant was proposed to provide a design method. The simulation results were similar to the measured data, and two schemes were proposed to improve the speed of an electromagnetic actuator.